Complex Parkinson's disease: review and experiences. (2nd June 2019) - Cotterell, Phil; Weight, Debbie; Joseph, Sharon; Joseph, Paul
Abstract : The rate of Parkinson's disease progression is highly individual. It is important to identify those in the complex stage of the disease. Non-oral therapies may be appropriate for those in the complex stage of the disease who experience motor fluctuations, but there can be reasons for a failure to explore these options. Complex Parkinson's disease is a challenging time for the patient, their carer/s and for Parkinson's specialists. Changes to independence can be difficult to deal with, and the disease has an impact both physically and psychologically. For carers, the impact of Parkinson's can also result in physical and psychological issues as well as social and financial problems. Consideration often turns to moving into a care environment, dealing with neuropsychiatric issues and challenging unmet need. Dealing with symptoms and problems using a team and a palliative approach is required.